In utero arsenic exposure and early childhood motor development in the New Hampshire Birth Cohort Study - Butler, Erin E.; Karagas, Margaret R.; Demidenko, Eugene; Bellinger, David C.; Korrick, Susan A. (Frontiers in Epidemiology, 2023)
High-level prenatal and childhood arsenic (As) exposure characteristic of several regions in Asia (e.g., Bangladesh), may impact motor function. However, the relationship between lower-level arsenic exposure (characteristic of other regions) and motor development is largely unstudied, despite the potential for deficient motor skills in childhood to have adverse long-term consequences. Thus, we sought to investigate the association between prenatal As exposure and motor function among 395 children in the New Hampshire Birth Cohort Study, a rural cohort from northern New England. Prenatal exposure was estimated by measuring maternal urine speciated As at 24–28 weeks of gestation using high-performance liquid chromatography (HPLC) inductively coupled plasma mass spectrometry (ICP-MS) and summing inorganic As, monomethylarsonic acid, and dimethylarsinic acid to obtain total urinary As (tAs). Motor function was assessed with the Bruininks-Oseretsky Test of Motor Proficiency, 2nd Edition (BOT-2) at a mean (SD) age of 5.5 (0.4) years. Children were largely reported as white race (97%), born to married mothers (86%) with a college degree or higher (67%). The median (IQR) gestational urine tAs concentration was 4.0 (5.0) µg/L. Mean (SD) BOT-2 scores were 48.6 (8.4) for overall motor proficiency and 48.2 (9.6) for fine manual control (standard score = 50 (10)), and were 16.3 (5.1) for fine motor integration and 12.5 (4.1) for fine motor precision (standard score = 15 (5)). We found evidence of a non-linear dose response relationship and used a change-point model to assess the association of tAs with overall motor proficiency and indices of fine motor integration, fine motor precision, and their composite, fine manual control, adjusted for age and sex. In models adjusted for potential confounders, each doubling of urine tAs decreased overall motor proficiency by –3.3 points (95% CI: –6.1, –0.4) for tAs concentrations greater than the change point of 9.5 µg/L and decreased fine motor integration by –4.3 points (95% CI: –8.0, –0.6) for tAs concentrations greater than the change point of 17.0 µg/L. In summary, we found that levels of prenatal As exposure above an empirically-derived threshold (i.e., the change point) were associated with decrements in childhood motor development in a US population.